1992
DOI: 10.1002/1097-0142(19920101)69:1<175::aid-cncr2820690129>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

High-dose-rate remote afterloading intracavitary radiation therapy for cancer of the uterine cervix. A 20-year experience

Abstract: Retrospective analysis was performed on 1022 patients with squamous cell carcinoma of the uterine cervix who were treated with high‐dose‐rate remote afterloading intracavitary irradiation at the National Institute of Radiological Sciences, Angawa, Chiba‐shi, Japan, from 1968 to 1982 in comparison with low‐dose‐rate intracavitary radiation therapy. The patient population consisted of 147 patients with Stage I disease, 256 patients with Stage II disease, 515 patients with Stage III disease, and 104 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(47 citation statements)
references
References 14 publications
0
45
0
2
Order By: Relevance
“…To achieve equivalent disease control to that achieved with LDR treatment without increasing the risk of late complications, various dosages and fractionation schedules of HDR-ICBT have been examined. Several studies, including nonrandomized [3][4][5][6][7][8][9] and randomized 10 -12 clinical trials, have demonstrated that HDR-ICBT was comparable to LDR-ICBT in terms of local control, survival, and morbidity rates. However, various fractionation schedules exist, and the optimum dose and fractionation schedule of ICBT and the appropriate combination of EBRT and ICBT remain controversial issues.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve equivalent disease control to that achieved with LDR treatment without increasing the risk of late complications, various dosages and fractionation schedules of HDR-ICBT have been examined. Several studies, including nonrandomized [3][4][5][6][7][8][9] and randomized 10 -12 clinical trials, have demonstrated that HDR-ICBT was comparable to LDR-ICBT in terms of local control, survival, and morbidity rates. However, various fractionation schedules exist, and the optimum dose and fractionation schedule of ICBT and the appropriate combination of EBRT and ICBT remain controversial issues.…”
mentioning
confidence: 99%
“…However, to our knowledge there have been only a very few studies published to date in which disease status and late complications were monitored for Ͼ 10 years after treatment, although HDR-ICBT has been used extensively in Asia and Europe for Ͼ 3 decades. [3][4][5][7][8][9][10][11][12] Therefore, the safety of HDR treatment has not been investigated thoroughly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HDR proved to be as clinically effective as LDR in the management of cervical cancer. In rates of survival, relapse and complications, no statistically significant differences have been found between both treatment methods 2,3,4,14,15,16,17 .…”
Section: Discussionmentioning
confidence: 89%
“…Details of IV 7 the protocol have been reported elsewhere. 18 Gy. Along with the central shielding irradiation, these Total 64 patients also received intracavitary irradiation by remote afterloading system using 60 Co sources; they received 4 insertions (1 per week) with fraction doses of 550 Centigray (cGy) to 600 cGy at point A.…”
mentioning
confidence: 99%